Stemflow Variability in Tropical Lowland Forest Landscape Transformation System: Case Study at Jambi Province, Indonesia - Bejo Slamet; I Nengah Surati Jaya; Hendrayanto Hendrayanto; Suria Darma Tarigan (Institut Pertanian Bogor (IPB University), 2015)
Land cover change may cause change on the hydrological function of an area, particularly on the distribution of rainfall that reach land surface. This study describes the characteristic of stemflow occurred within 4 ecosystems in Jambi, namely logged forest, jungle rubber, rubber plantation, and oil palm plantation. The main objective of the study was to measure the variability of stemflow in those 4 ecosystems. The main data used were rainfall and stemflow data that were directly measured for 5 months. The derived regression equation model showed that stemflow increase with rainfall depth. It was shown that values of stemflow amongs plantation types was varied indicated by the difference of its regression coefficients, as well as variations of the rainfall at the same transformation type. The percentage of stemflow to rainfall was ranging from 0.04–0.21% for rubber, 0.10–0.38% for jungle rubber, 0.28–0.54% for forest, and 0.84–3.07% for oil palm. The oil palm provided the highest stemflow volume compared to other land cover type. The uniqueness of oil palm canopy may cause the drainage of water from the canopy to the main stem that indicated by highest stemflow funneling ratio value. Rainfall significantly affected the amount of stemflow compared with the characteristics of the plant.